Genetic Association between Akt1 Polymorphisms and Alzheimer's Disease in a Japanese Population. (14th July 2011) - Shibata, Nobuto; Ohnuma, Tohru; Kuerban, Bolati; Komatsu, Miwa; Baba, Hajime; Arai, Heii
Abstract : A recent paper reported that A β oligomer causes neuronal cell death through the phosphatidylinositol-3-OH kinase (PI3K)-Akt-mTOR signaling pathway. Intraneuronal A β, a main pathological finding of Alzheimer's disease (AD), is also known as inhibiting activation of Akt. This study aims to investigate whether single nucleotide polymorphisms (SNPs) of the Akt1 gene are associated with AD. SNPs genotyped using TaqMan technology was analyzed using a case-control study design. Our case-control dataset consisted of 180 AD patients and 130 age-matched controls. Although two SNPs showed superficial positive, Hardy-Weinberg equilibrium (HWE) tests, and linkage disequilibrium (LD) analyses suggested that genetic regions of the gene are highly polymorphic. We failed to detect any synergetic association among Akt1 polymorphisms, Apolipoprotein E (APO E), and AD. Further genetic studies are needed to clarify the relationship between the Akt1 and AD.